THE MERIT SYSTEM ON THE ACT NO. 20 OF 2023 ABOUT THE STATE'S CIVIL APPARATUS AND PUBLIC SERVICES - Muin, Fatkhul (SUPREMASI HUKUM, 2024)
Efforts to create a good government system are correlated with the government system built in government to achieve government goals through good employee management. Law no. 20 of 2023 concerning State Civil Apparatus. The main aim of having a merit system in positions is an effort to create a good service system for society. Therefore, the essence of Law no. 20 of 2023 in order to accelerate the implementation of the transformation of the state civil apparatus to create a state civil apparatus with high work results and behavior that is service-oriented, accountable, competent, harmonious, loyal, adaptive and collaborative, it is necessary to improve the implementation of the management of the state civil apparatus. This research uses a legal approach by analyzing the legal policy of an employee merit system in order to improve public services. Keywords: Merit System, Legal Policy, Public Service